2001
DOI: 10.1111/j.1095-8312.2001.tb01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratification and diel activity of arthropods in a lowland rainforest in Gabon

Abstract: The abundance, activity and species richness of arthropods, particularly of insect herbivores, were investigated in the upper canopy and understorey of a lowland rainforest at La Makande, Gabon. In total 14 161 arthropods were collected with beating, flight interception and sticky traps, from six canopy sites, during the day and at night, from midJanuary to mid-March 1999. The effects of stratum were most important, representing between 40 and 70% of the explained variance in arthropod distribution. Site effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 38 publications
2
76
0
11
Order By: Relevance
“…Studying upper-canopy leaves from across the Amazon Basin, Fyllas et al (2009) also observed significant variations in foliar carbon content, relating this to variations in M A and the extent of investment in constitutive defenses. Consistent with this and the observed positive vertical gradient in [C] DW both between and within trees is the tendency for leaves higher up rain forest canopies to have greater levels of carbon based defense compounds (Lowman and Box, 1983;Downum et al, 2001;Dominy et al, 2003), this perhaps being associated with higher abundances of herbivores such as insects and other arthropods also occurring there (Sutton, 1989;Kato et al, 1995;Koike et al, 1998;Basset et al, 2001).…”
Section: Gradients In Carbon and Cation Concentrationsmentioning
confidence: 74%
“…Studying upper-canopy leaves from across the Amazon Basin, Fyllas et al (2009) also observed significant variations in foliar carbon content, relating this to variations in M A and the extent of investment in constitutive defenses. Consistent with this and the observed positive vertical gradient in [C] DW both between and within trees is the tendency for leaves higher up rain forest canopies to have greater levels of carbon based defense compounds (Lowman and Box, 1983;Downum et al, 2001;Dominy et al, 2003), this perhaps being associated with higher abundances of herbivores such as insects and other arthropods also occurring there (Sutton, 1989;Kato et al, 1995;Koike et al, 1998;Basset et al, 2001).…”
Section: Gradients In Carbon and Cation Concentrationsmentioning
confidence: 74%
“…Certainly, a high insect abundance (i.e., bat food) has been associated with the canopy of Neotropical rainforests [72][73][74], as food resources for phytophagous insects (e.g., foliage, flowers, fruits) are more abundant in the canopy [75], and there is a greater diversity of niches than in the midstory or understory [76].…”
Section: Discussionmentioning
confidence: 99%
“…Note also that the real value of areas scanned are likely to be smaller than ulτ 1 , as far as arthropods are only active during some parts of the day (Basset et al, 2001). We thus conclude that arthropod runners, crawlers and walkers with linear body size not exceeding several millimetres can yet be residents.…”
Section: Residents Versus Travellers: Soil Microorganisms and Arthropmentioning
confidence: 99%